Patterns of Aedes aegypti immature ecology and arboviral epidemic risks in peri-urban and intra-urban villages of Cocody-Bingerville, Côte d’Ivoire: Insights from a dengue outbreak - Yasmine N. Biré; Julien Z. B. Zahouli; Jean D. K. Dibo; Pierre N. Coulibaly; Prince G. Manouana; Jacques F. Mavoungou; Fanny Hellhammer; Gaël D. Maganga; Luc S. Djogbenou; Ayola A. Adegnika; Steffen Borrmann; Stefanie C. Becker; et al. (PLoS ONE, 2026)
Background Cocody-Bingerville, southeastern Côte d’Ivoire, a traditional focus of yellow fever (YF), has faced outbreaks of dengue (DEN) that caused 4,371 cases and 29 deaths from 2023–2024. However, local Aedes vector studies and arboviral outbreak responses have mostly focused on urban neighborhoods including intra-urban villages, but no prior research has been done in peripheral villages. We compared Aedes aegypti indices, container productivity, and DEN and YF epidemic risks between peri-urban and intra-urban villages during the outbreaks. Methods From August 2023 to July 2024, we sampled Aedes eggs, larvae and pupae among three peri-urban and three intra-urban villages. Sampling was done in domestic and peridomestic ecozones of 100 households in each village per survey, and uniformly across four climatic seasons: short dry, short rainy, long dry, and long rainy seasons. We compared Ae. aegypti container productivity, Stegomyia indices (house index: HI, container index: CI, and Breteau index: BI) and pupal indices (pupae per house index: PHI, pupae per container index: PCI, and pupae per person index: PPI) across villages, ecozones and seasons. Results Aedes aegypti widely dominated Aedes fauna in both peri-urban (98.1%) and intra-urban (99.8%) villages. The most productive containers were small containers (31.1%), tires (30.5%) and medium containers (20.1%) in the peri-urban villages, and tires (64.6%) and small containers (18.7%) in the intra-urban villages that yielded over 80% of all the pupae collected in each village type. These key containers produced substantially more pupae in the domestic ecozones (70.9%) in the peri-urban villages, but equitably between the domestic (48.8%) and peridomestic (51.2%) ecozones in the intra-urban villages. In all villages, key containers provided over 80% of pupae sampled during short dry and long rainy seasons. CI, HI and BI were comparable between the peri-urban (29.9%, 35.9% and 41.4) and intra-urban (36.7%, 48.0% and 56.2) villages. However, PCI (3.38 vs . 1.26 pupae/container), PHI (5.18 vs. 1.75 pupae/house) and PPI (1.25 vs . 0.54 pupae/person) values were, respectively, 2.7, 3.0 and 2.3-fold higher in the intra-urban compared to peri-urban villages. Lower pupal indices in the intra-urban villages were compensated by five additional Aedes vector species. All indices were correlated to rainfall in all villages, with correlation coefficients varying from 0.16 to 0.84. Conclusion In Cocody-Bingerville, all sampled peri-urban and intra-urban villages hosted high densities of Ae. aegypti immatures and habitats (tires, small or medium containers). Stegomyia indices remained consistently high, exceeding WHO DEN and YF epidemic thresholds in all villages, potentially contributing to ongoing DEN outbreaks. Aedes vector surveillance and outbreak responses should be extended to peri-urban villages, as they are likely contributors to arbovirus persistence and reintroduction. This is the first study to directly compare Aedes indices across peri-urban and intra-urban settings during an arboviral outbreak and offers a baseline for strategically reducing human exposure. Community-led interventions (larval source reduction, larviciding, public awareness) targeting identified larval habitats could help control arboviral outbreaks.